Treatment of Erectile Dysfunction in a Hypogonadal Male - Mulhall, John P (MedReviews, LLC, 2004)
Anecdotal evidence suggests that hypogonadal men who failed to respond to sildenafil citrate changed their response when supplemented with androgens. The author presents the case of a middle-aged man with hypogonadism who experienced success with sildenafil citrate with supplemental testosterone.